Clinical and Imaging Characteristics of Metastatic Orbital Tumours in North China - Yun Zhao; Shasha Yu; Mengxia Mu; Jiagen Li; Hongxun Li; Hong Zhao (Journal of Ophthalmology)
Purpose. This study was designed to review the primary sites, clinical manifestations, imaging features, treatments, and outcomes of 36 patients with orbital metastasis in North China. Methods. This was a retrospective review of 36 patients with orbital metastasis at Tianjin Eye Hospital between January 2010 and December 2020 in North China as well as a review of the literature. Results. Thirty-six patients were included in the study; 17 were male, and 19 were female, with an age range of 1–82 years (average 54.9 ± 19.8 years). All the tumours were unilateral. The mean duration from the onset of orbital signs to presentation at the hospital was 2.4 months (range 1–10 months). Breast carcinoma, gastrointestinal tract carcinoma, and lung carcinoma were the most common histological types. Proptosis, ocular pain, and diplopia were the most common clinical manifestations. The superior orbit was the most common quadrant involved. All patients received comprehensive therapy, including surgery, radiotherapy, or chemotherapy. The average follow-up time was 2.45 years (range 7 months to 5.5 years). Ten patients in this study died as a result of disseminated metastasis from the primary tumour. Conclusions. In North China, the most common primary cancer that metastasizes to the orbit is breast cancer, followed by gastrointestinal tract carcinoma and lung cancer. The increasing trend of orbital gastrointestinal tract metastases in North China in recent years is noteworthy. The survival rate of patients with orbital metastasis of neuroblastoma is low.